2006
DOI: 10.1002/ppap.200500110
|View full text |Cite
|
Sign up to set email alerts
|

Electrical and Optical Characteristics of Ta2O5 Thin Films Deposited by Electron‐Beam Vapor Deposition

Abstract: Summary: Ta2O5 is a material with good perspectives for many applications in modern electronics and information technologies. Several deposition techniques of thin Ta2O5 films have been suggested. Reliable information is still needed, however, on structural, electrical and optical parameters of the films, and their dependence on the deposition technique. We have deposited Ta2O5 thin films by electron‐beam evaporation of Ta2O5 powder onto Si, tantalum and glass substrates. The resistivity of the films with vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 18 publications
(13 reference statements)
0
7
0
Order By: Relevance
“…In this work, we use a graphene/Ta 2 O 5 /graphene heterostructure to demonstrate optoelectronic synapses . Ta 2 O 5 has shown good platform on CMOS technology 34 , 35 . It also has a high energy bandgap of ~ 4 eV which facilitates the realization of optoelectronic synaptic characteristics in the visible spectrum 36 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this work, we use a graphene/Ta 2 O 5 /graphene heterostructure to demonstrate optoelectronic synapses . Ta 2 O 5 has shown good platform on CMOS technology 34 , 35 . It also has a high energy bandgap of ~ 4 eV which facilitates the realization of optoelectronic synaptic characteristics in the visible spectrum 36 .…”
Section: Introductionmentioning
confidence: 99%
“…It also has a high energy bandgap of ~ 4 eV which facilitates the realization of optoelectronic synaptic characteristics in the visible spectrum 36 . It has been shown that Ta 2 O 5 deposited by e-beam instead of RF sputtering gives a narrow gap of visible light absorption 34 , 35 , 37 . which is the mechanism used for deposition in this work.…”
Section: Introductionmentioning
confidence: 99%
“…deposition [14,15], electron-beam evaporation [16,17], ion-beam sputter deposition [18,19], sol-gel spinning coating [20], PLD [21] and so on. For PLD method, it is easy to yield substoichiometric tantalum oxide (TaO x , x<2.5) films resulted from deficiency of oxygen.…”
Section: Introductionmentioning
confidence: 99%
“…Ta 2 O 5 is one of the more commonly used high refractive index materials in multilayer dielectric mirrors due to their high transmittance and low optical loss [5,6]. Various techniques have been used to deposit tantalum pentoxide thin films such as reactive magnetron sputtering [7], electron-beam evaporation [8], ion beam sputtering [9], and ion-assisted deposition [6]. Using these methods, film properties were reported [10][11][12].…”
Section: Introductionmentioning
confidence: 99%